Electroconvulsive therapy for depression : optimising treatment and exploring molecular mechanisms - Kolshus, Erik (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Psychiatry, 2016)
The objective of this project was to explore clinical and molecular aspects of electroconvulsive therapy (ECT) in the treatment of depression, with a particular focus on the role of microRNAs (small, non-coding molecules that can regulate gene expression). The patients receiving ECT in this study were participants in a randomised controlled trial (the EFFECT-Dep Trial) of high-dose (6x seizure threshold) right unilateral and standard dose (1.5x seizure threshold) bitemporal brief-pulse ECT for depression. The objective of the EFFECT-Dep Trial was to compare the effectiveness and cognitive side-effects of these two forms of ECT. In this thesis, a systematic review and meta-analysis was carried out with a similar objective. PubMed, PsycInfo, Web of Science, Cochrane Library, Embase and the International Clinical Trials Registry Platform databases were searched for with the terms "electroconvulsive" or "electroshock" and "trial". Seven randomised controlled trials (n=792) met inclusion criteria, including the EFFECT-Dep Trial. Bitemporal ECT did not differ from high-dose unilateral ECT on depression rating change scores (Hedges’s g = -0.03; 95% confidence interval (CI) -0.17 to 0.11), remission (RR 1.06; 95% CI 0.93 to 1.20), or relapse at 12-months (RR 1.42; 95% CI 0.90 to 2.23). There was an advantage for unilateral ECT on reorientation time after individual ECT sessions (mean difference in minutes = -8.28; 95% CI -12.86 to -3.70) and retrograde autobiographical memory (Hedges’s g =-0.46, 95% CI=-0.87 to -0.04) after completing an ECT course. There were no differences for general cognition, category fluency and delayed visual and verbal memory. The immediate clinical implication of this is that high-dose right unilateral ECT should be considered as a first-line option when prescribing ECT. Peripheral blood samples from patients participating in the EFFECTDep Trial and healthy controls were collected in PaxGene© bottles. MicroRNAs and mRNAs were extracted using PaxGene© blood miRNA/RNA kits. An initial discovery phase deep sequencing study (n=16) was carried out on the SOLiD™ platform. This yielded over 23 million reads mapping on to known microRNAs in the human genome. However, in the group as a whole there were no significant differences in microRNA levels from baseline to ECT following strict correction for multiple testing. However, post-hoc analysis indicated that there were significant changes in microRNA levels in patients with psychotic depression. These changes were confirmed in the same sample using quantitative real-time polymerase chain reaction (qRTPCR). In a separate cohort (37 depressed, 34 controls), candidate microRNAs from deep sequencing were analysed in a validation study. Two microRNAs (miR-126-3p and miR-106a-5p) were significantly elevated in patients with psychotic depression (n=7) at baseline when compared to healthy controls. After ECT treatment, the levels of these microRNAs normalised. Bioinformatic analysis revealed a high number of genes, molecular and biological processes as well as signalling pathways targeted by miR- 126-3p and miR-106a-5p. VEGFA, SIRT1 and E2F1 were shared gene targets of both microRNAs. Molecular and biological processes involving genes targeted by miR-126-3p and miR-106a-5p revealed that cell cycle regulation, regulation of transferase activity and response to abiotic stimuli were particularly over-represented. A number of over-represented pathways relevant to depression and the potential mechanism of ECT were identified. These included several growth factor pathways (VEGF, IGF, TGF-Beta, PDGF, EGF) and cell cycle regulatory pathways implicated in depression and neuroplasticity. Downstream VEGFA mRNA levels were subsequently quantified using qRT-PCR (97 depressed, 53 controls). VEGFA mRNA levels were raised in depressed (psychotic and non-psychotic) subjects compared to healthy controls. Following ECT however, there was a significant decrease in VEGFA levels in the psychotic depression group (n=21) only. VEGFA levels correlated with psychotic symptomatology, but no correlations with cognitive outcomes were observed. There was no effect of electrode placement on VEGFA levels. The objective of this project was to explore clinical and molecular aspects of electroconvulsive therapy (ECT) in the treatment of depression, with a particular focus on the role of microRNAs (small, non-coding molecules that can regulate gene expression). The patients receiving ECT in this study were participants in a randomised controlled trial (the EFFECT-Dep Trial) of high-dose (6x seizure threshold) right unilateral and standard dose (1.5x seizure threshold) bitemporal brief-pulse ECT for depression. The objective of the EFFECT-Dep Trial was to compare the effectiveness and cognitive side-effects of these two forms of ECT. In this thesis, a systematic review and meta-analysis was carried out with a similar objective. PubMed, PsycInfo, Web of Science, Cochrane Library, Embase and the International Clinical Trials Registry Platform databases were searched for with the terms "electroconvulsive" or "electroshock" and "trial". Seven randomised controlled trials (n=792) met inclusion criteria, including the EFFECT-Dep Trial. Bitemporal ECT did not differ from high-dose unilateral ECT on depression rating change scores (Hedges’s g = -0.03; 95% confidence interval (CI) -0.17 to 0.11), remission (RR 1.06; 95% CI 0.93 to 1.20), or relapse at 12-months (RR 1.42; 95% CI 0.90 to 2.23). There was an advantage for unilateral ECT on reorientation time after individual ECT sessions (mean difference in minutes = -8.28; 95% CI -12.86 to -3.70) and retrograde autobiographical memory (Hedges’s g =-0.46, 95% CI=-0.87 to -0.04) after completing an ECT course. There were no differences for general cognition, category fluency and delayed visual and verbal memory. The immediate clinical implication of this is that high-dose right unilateral ECT should be considered as a first-line option when prescribing ECT. Peripheral blood samples from patients participating in the EFFECTDep Trial and healthy controls were collected in PaxGene© bottles. MicroRNAs and mRNAs were extracted using PaxGene© blood miRNA/RNA kits. An initial discovery phase deep sequencing study (n=16) was carried out on the SOLiD™ platform. This yielded over 23 million reads mapping on to known microRNAs in the human genome. However, in the group as a whole there were no significant differences in microRNA levels from baseline to ECT following strict correction for multiple testing. However, post-hoc analysis indicated that there were significant changes in microRNA levels in patients with psychotic depression. These changes were confirmed in the same sample using quantitative real-time polymerase chain reaction (qRTPCR). In a separate cohort (37 depressed, 34 controls), candidate microRNAs from deep sequencing were analysed in a validation study. Two microRNAs (miR-126-3p and miR-106a-5p) were significantly elevated in patients with psychotic depression (n=7) at baseline when compared to healthy controls. After ECT treatment, the levels of these microRNAs normalised. Bioinformatic analysis revealed a high number of genes, molecular and biological processes as well as signalling pathways targeted by miR- 126-3p and miR-106a-5p. VEGFA, SIRT1 and E2F1 were shared gene targets of both microRNAs. Molecular and biological processes involving genes targeted by miR-126-3p and miR-106a-5p revealed that cell cycle regulation, regulation of transferase activity and response to abiotic stimuli were particularly over-represented. A number of over-represented pathways relevant to depression and the potential mechanism of ECT were identified. These included several growth factor pathways (VEGF, IGF, TGF-Beta, PDGF, EGF) and cell cycle regulatory pathways implicated in depression and neuroplasticity. Downstream VEGFA mRNA levels were subsequently quantified using qRT-PCR (97 depressed, 53 controls). VEGFA mRNA levels were raised in depressed (psychotic and non-psychotic) subjects compared to healthy controls. Following ECT however, there was a significant decrease in VEGFA levels in the psychotic depression group (n=21) only. VEGFA levels correlated with psychotic symptomatology, but no correlations with cognitive outcomes were observed. There was no effect of electrode placement on VEGFA levels.
Keywords: Psychiatry, Ph.D.; Ph.D. Trinity College Dublin